AKTIVITAS ANTIBAKTERI JAMU MADURA SUBUR KANDUNGAN - Wijayanto, Andik; Abrori, Romi (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2015)
Madurese traditional medicine (herbs) Subur Kandungan is a medicine that is widely used and produced in Madura that contains Curcuma zedoaria (Chrism.)Rosc., Kaempferia galanga L., Foeniculum vulgare Mill., and Centella asiatica (L.)Urb. highly favoredby the Indonesian community, especially women to improve reproductive health but have not been tested scientifically and standardization to ensure efficacy and safety. Initial stageis screening bioactive compound and then antibacterial activity assay with paper disc method. Clinical bacterial isolates such as Escherichia coli and Staphylococcus aureus were used as test organisms. The best treatment to inhibit the growth of E. Coli and S. aureusis 70% ethanol at a concentration of extract 1000 mg/ml with inhibition zone respectively 5mm and 6.5mm. Although in crude extract form, Madurese traditional medicine (herbs) Subur Kandungan had inhibitory effect on the growth of the E.coli and S.aureus so this traditional medicine potential as an antibacterial agent. It is recommended that further work be done to identify the specific secondary metabolite compound that responsible for this effect, purify it, and standardize as same as a antibacterial drug.